THE BANKING UNION – THE SOLUTION TO REDUCE THE EUROPEAN BANKING SYSTEM RISKS? - ALINA LIGIA DUMITRESCU (Global Economic Observer)
The banking union has been seen as "a panacea" for solving the system risks of the EU banking system. This paper objectives are to find out if is the banking union, with is strong and week sides, will be right answer to solve the actual issues that EU banking system has as: the fragmentation in the EU single market, the deterioration in asset quality, the need for recapitalization and the quality of banks’ loan portfolios. According with most of the experts the banking union will strength the process of economic integration. On the other side, the non-euro area member states are questioning about "equal rights and obligations for all Member States" inside the banking union. But, with all pros and cons of the banking union, the ECB's making decisions and tasks can be questioned, although its role of supervisor can not be disputed. The most important thing is that the banking union breaks the vicious circle between banks and sovereign debts, and ends "to big to fail"